Seasonal variation in C:N:P stoichiometry, nonstructural carbohydrates, and carbon isotopes of two coniferous pioneer tree species in subtropical China - Liu, Yuanxi; Xiao, Jiandong; Sun, Jianli; Zhao, Zhijuan; Deng, Xin; Wu, Junwen; Zhang, Deguo; Bao, Yun (Frontiers in Plant Science, 2023)
The characteristics of C:N:P stoichiometry, nonstructural carbohydrate (NSC) content, and C stable isotopes and their relationships affect plant responses to environmental changes and are critical to understanding the ecosystem carbon and water cycles. We investigated the water use strategies and physiological changes of two pioneer tree species (Pinus armandii and Pinus yunnanensis) in response to seasonal drought in subtropical China. The seasonal variation in needle δ13C values, C:N:P stoichiometry, and NSC contents of the two tree species were studied in 25-year-old plantation in central Yunnan Province. The needle δ13C values of both species were highest in summer. Soluble sugars, starch and NSC content of the two tree species decreased from spring to winter, while there was no significant difference in the seasonal variation of soluble sugars/starch in P. armandii needles, the maximum soluble sugars/starch in P. yunnanensis needles was in autumn. In addition, the C, N, and P contents of the needles and the C:N and C:P ratios of the two species showed different seasonal fluctuations, whereas the N:P ratio decreased with the season. The C:N:P stoichiometry and NSC content of the needles showed significant correlations, whereas the needle δ13C was weakly correlated with C:N:P stoichiometry and NSC content. Phenotypic plasticity analysis and principal component analysis revealed that the needle nutrient characteristics (NSC and P contents and N:P ratio) and needle δ13C values were critical indicators of physiological adaptation strategies of P. armandii and P. yunnanensis for coping with seasonal variation. These results increase our understanding of the water-use characteristics of the two pioneer tree species and the dynamic balance between the NSC, C, N, and P contents of the needles.